THE EFFECT OF STORYTELLING ON THE ELEVENTH GRADE STUDENTS SPEAKING SKILL - Yusuf Mahendra; Anshari Syafar (e-Journal of ELTS (English Language Teaching Society), 2021)
The objective of this research is to find out the effect of storytelling on the development of students’ speaking skill in teaching English. The sample of this research was the eleventh grade students. The research sample were selected using convenience sampling technique. The research applied quasi-experimental design. The data were collected through pretest and posttest. The data were analyzed using t-test to compare mean score of pretest and posttest of experimental and control group. The result showed that the mean differences of the experimental and control group students were (51.70) and (52.75) in pretest. While the posttest were (60.23) and (54.50). Further analysis indicates, t-counted (4.57) is greater than t-table (2.02). The control group got the higher score on pretest while the experimental group got the higher score on posttest which is mean that the hypothesis of the research failed to be rejected. In other word, the use of storytelling to teach English has impact in improving students’ speaking ability.